Voiding Pattern in Thai Female without Lower Urinary Tract Symptoms - Arunratsamee, Pattarawin; Bunyavejchevin, Suvit (Thai Journal of Obstetrics and Gynaecology, 2019)
Objective: To study the parameters of voiding patterns in Thai women without LUTS and to compare the voiding parameters between different age groups and menopausal status. Material and Method: Seventy Thai women who live or work in various communities in Thailand without LUTS were invited to participate in the study during May- September, 2015. The volunteers were asked to complete Thai version Urogenital Distress Inventory (UDI) for screening of LUTS for exclusion. All cases were trained how to collect and record in 3-day bladder diary. Results: Two hundreds and ten bladder diaries (70 women; 3 days/1 person) were completed by seventy women. The mean + SD of age was 48.4 + 7.9 years, the BMI was 23.3+ 4.0 kg/m2, 25.7% were postmenopausal. The mean + SD of voiding parameters were: 7.4+2.3 times (24 hrs voiding frequency), 6.5+2.0 times (daytime frequency), 0.7 (0-3) times (night time frequency), and 1560+627 cc (daily voided volume).The increasing age was associated with higher 24-hr voiding frequency and daytime voiding frequency. Conclusion: The voiding parameters of Thai women without LUTS were reported. This data can be used as the tools for selecting Thai women with LUTS for further investigations and treatments. This result can be used as the reference for future research for the LUTS management.